2018
DOI: 10.1016/j.learninstruc.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal relations between students’ academic enjoyment, boredom, and achievement over time

Abstract: Reciprocal relations between students' academic enjoyment, boredom, and achievement over time http://researchonline.ljmu.ac.uk/id/eprint/7090/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Abstract The control-value theory (CVT) proposes that achievement emotions and academic achievement show reciprocal effects over time. Previous studies have examined how achievement emotions predict subsequent achievement. However, evidence is limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
89
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 54 publications
(53 reference statements)
14
89
3
5
Order By: Relevance
“…We also found that only SC interaction negatively predicted boredom. This finding was consistent with that by Putwain et al [13]. If learning materials are simple, students could be bored.…”
Section: Relationships Among Students' Interaction Academic Emotionssupporting
confidence: 92%
See 2 more Smart Citations
“…We also found that only SC interaction negatively predicted boredom. This finding was consistent with that by Putwain et al [13]. If learning materials are simple, students could be bored.…”
Section: Relationships Among Students' Interaction Academic Emotionssupporting
confidence: 92%
“…According to the control-value theory [49], academic emotions can be distinguished along dimensions of activation (activating vs. deactivating), valence (positive vs. negative), and object focus (activity vs. outcome). Although several different academic emotions can be induced in online learning conditions, the present study emphasizes the detailed effects of academic emotions (enjoyment, anxiety, and boredom) because they are the most frequently and intensely academic emotions experienced in online learning environments [13].…”
Section: Academic Emotionsmentioning
confidence: 86%
See 1 more Smart Citation
“…Firstly, it was found to have effects on students' class-related emotions, achievement goals, task value, self-efficacy in learning, learning engagement, use of learning strategies, and behavior problems [15][16][17]. Secondly, research found that students' class-related boredom affected their achievement and performance [14,18,19]. Lastly, students' class-related boredom was confirmed to have an influence on learning burnout [20], career aspirations [21], and lifelong learning [22].…”
Section: Class-related Boredommentioning
confidence: 99%
“…Estas observaciones apoyan la teoría psicológica del Control-Valor (Pekrun, 2006), que explica cómo las emociones de los individuos, en relación con las actividades de enseñanza-aprendizaje, están moduladas por el control sobre esas actividades y por el valor esperado. Así, las emociones experimentadas durante el desarrollo de las actividades y tras los resultados de aprendizaje influyen tanto en la estimación del valor de futuros procesos de enseñanza-aprendizaje como en sus resultados (Pekrun et al, 2014;Putwain et al, 2017). Algunos estudios apoyan que, en el caso de las Matemáticas (asignatura relacionada con emociones como nerviosismo o ansiedad), su aprendizaje duradero podría estar mediado por las emociones experimentadas durante su adquisición (Murayama et al, 2013;Pekrun et al 2017).…”
Section: El Aprendizaje Condiciona Las Emocionesunclassified